Preparation and properties of methyl methacrylate and fluoroacrylate copolymers for plastic optical fiber cladding - Choi, DI; Yeom, EH; Park, M; Kim, JK; Kim, BC (WILEY-BLACKWELL, 2004)
Copolymers of methyl methacrylate (MMA) and fluoroacrylate (FA), with different FA content (0-100 wt %), were prepared by bulk polymerization. The chemical structure was identified by H-1-NMR and other physical properties were measured by DSC, Abbe refractometer, X-ray diffractometry, polarized optical microscopy, and DMA. The copolymers were confirmed as random copolymers by Fineman-Ross analysis and first-order Markov statistics. Increasing the FA content from 0 to 100 wt % decreased the refractive index from 1.492 to 1.368. Copolymers with FA content higher than 70 wt % crystallized and led to low transparency and poor thermal properties. On the other hand, copolymers with FA content lower than 70 wt % was thermally stable (T-g was as high as 60degreesC) and transparent. (C) 2004 Wiley Periodicals, Inc.
Keywords: POLYMER FIBERS